2017
DOI: 10.5385/nm.2017.24.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Severe Peripheral Tissue Ischemia after Arterial Catheterization in Micro Preemies using Humidification & Topical Nitroglycerin

Abstract: Micro preemies usually undergo arterial catheterization for frequent blood pressure monitoring and blood sampling. Peripheral tissue injury associated arterial cathe terization is a well described morbidity observed in neonates. Despite the potential permanent disability associated with this complication, the currently available thera peutic options remain limited. We report a unique case of a preterm infant who de veloped severe tissue ischemia after arterial catheterization of the radial artery and was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The logistic analysis showed that the factors affecting peripheral arterial ischemia were lower gestational age, lower birth weight, lower 1-minute Apgar scores, lower 5-minute Apgar scores, occurrence of PDA, the duration of inotropic agent use, the duration of ventilator treatment, and the duration of in-dwelling umbilical arterial lines. The factors affecting peripheral arterial ischemia were the duration of umbilical artery catheterization, which was also identified as a cause of peripheral arterial ischemia by Teo and Shah [20], Rizzi et al [21], and Han et al [9]. In the study of Samiee-Zafarghandy et al [8], a low Apgar score, lower gestational age (26+4 weeks), and ven-tilator treatment were also identified as significant factors, as in this study.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The logistic analysis showed that the factors affecting peripheral arterial ischemia were lower gestational age, lower birth weight, lower 1-minute Apgar scores, lower 5-minute Apgar scores, occurrence of PDA, the duration of inotropic agent use, the duration of ventilator treatment, and the duration of in-dwelling umbilical arterial lines. The factors affecting peripheral arterial ischemia were the duration of umbilical artery catheterization, which was also identified as a cause of peripheral arterial ischemia by Teo and Shah [20], Rizzi et al [21], and Han et al [9]. In the study of Samiee-Zafarghandy et al [8], a low Apgar score, lower gestational age (26+4 weeks), and ven-tilator treatment were also identified as significant factors, as in this study.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, it was also found that the application of nitroglycerin patches in premature newborns with peripheral arterial ischemia resulted in improvements in 83.3% of patients. Specifically, premature newborns without necrosis showed improvement within an average of 4.32 days and those with necrosis showed improvement within an average of 7.50 days, indicating that patches led to faster improvements than the 2 weeks needed for improvements in response to ointments in earlier studies [9].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…An ointment is also more applicable in non-contiguous areas such as joints ( Generali and Cada, 2001 ). The most common dose of ointment employed in 16 subjects was 4 mm/kg ( Elboraee et al, 2018 , Han et al, 2017 , Samiee-Zafarghandy et al, 2014 , Akingbola et al, 2012 , Sardesai et al, 2011 , Mousavi et al, 2010 , Vasquez et al, 2003 , Baserga et al, 2002 , O’Reilly et al, 1988 ). The physiological effect commenced within one hour and lasted for approximately six hours ( Dilli et al, 2015 , Baserga et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%